Preclinical validation of electrospun fibers to achieve vaginal colonization by Lactobacillus crispatus - Armstrong, Christy N.; Saha, Sudeshna; Aagard, Marnie A.; Mahmoud, Mohamed Y.; Varki, Nissi M.; Gilbert, Nicole M.; Frieboes, Hermann B.; Lewis, Warren G.; Lewis, Amanda L. (Frontiers in Bacteriology, 2025)
IntroductionCommunities of bacteria collectively known as the vaginal microbiota reside in the human vagina. Bacterial vaginosis (BV) describes an imbalance of this microbiota, affecting more than 25% of women worldwide, and is linked to health problems such as infertility, cervical cancer, and preterm birth. Following antibiotic treatment, BV becomes recurrent in many individuals. Lactobacillus crispatus is widely believed to contribute to a healthy vaginal microbiome, and its therapeutic application has shown promise in early clinical trials investigating adjunct therapies for lasting treatment of conditions such as BV. There is a pressing need for therapeutic platforms that apply biologically active agents such as probiotic bacteria, to the vagina with little user effort but lasting effect.MethodsHere, we use a mouse model to investigate the functional utility and potential harms of soft, slow-dissolving fibers made by electrospinning polyethylene oxide (PEO) and poly(lactic-co-glycolic acid) (PLGA). Blank electrospun fibers that passed quality control checkpoints were administered vaginally in a murine model and compared to animals receiving mock procedures.ResultsFiber administration had no significant effects on mucus glycan markers, vaginal epithelial exfoliation, keratinization, tissue edema or neutrophil infiltration. L. crispatus-loaded fibers enabled L. crispatus colonization in most animals for more than one week. Mice receiving L. crispatus-loaded fibers had significantly higher measured concentrations of lactate in vaginal washes at 48 hrs compared to pre-colonization washes.DiscussionThese data provide pre-clinical proof of concept that vaginal administration of electrospun fibers can achieve viable delivery and vaginal colonization by metabolically active L. crispatus, without eliciting inflammation or injury.